Finding of an Ixodid Tick Inside a Late Holocene Owl Pellet From Northwestern Argentina - Sánchez, Juliana Patricia (2010)
In the present study, we report the earliest record of Ixodes sigelos from the late Holocene in Argentina. The tick was recovered from an owl pellet collected within a small mammal sequence in Las Mascaras Cave, Catamarca, Argentina (27º01´12´´S,66º44´37´´W) and dated at 990 ± 35 cal yr BP. Based on bones also present in the pellet, the tick most-likely parasitized a rodent, identified as an Eligmodontia sp., which had been ingested by the owl.